A Life-Based Citizenship Education Textbook for Vocational High Schools - Ikhsan, M. Alifudin (Universitas Negeri Malang, 2019)
This article discusses learning innovations for developing decent life-based textbooks in Vocational High Schools. The study produced a product in the form of a Pancasila and Citizenship Education textbook integrated with character values. This book was developed based on the characteristics of Vocational High School students, the character education content and applicable learning curriculum. The assessment of media experts, design and learning experts shows this learning book is valid. The results of trials on students indicate that this learning book can be used to improve the quality of learning, but a number of dimensions of special practicality need to be considered in the next testing phase.